Delays in the Reticulospinal System Are Associated With a Reduced Capacity to Learn a Simulated Feeding Task in Older Adults - Rangarajan, Vishvak; Schreiber, Joseph J.; Barragan, Beatriz; Schaefer, Sydney Y.; Honeycutt, Claire F. (Frontiers in Neural Circuits, 2022)
Learning declines with age. Recent evidence indicates that the brainstem may play an important role in learning and motor skill acquisition. Our objective was to determine if delays in the reticular formation, measured via the startle reflex, correspond to age-related deficits in learning and retention. We hypothesized that delays in the startle reflex would be linearly correlated to learning and retention deficits in older adults. To determine if associations were unique to the reticulospinal system, we also evaluated corticospinal contributions with transcranial magnetic stimulation. Our results showed a linear relationship between startle onset latency and percent learning and retention but no relationship between active or passive motor-evoked potential onsets or peak-to-peak amplitude. These results lay the foundation for further study to evaluate if 1) the reticular formation is a subcortical facilitator of skill acquisition and 2) processing delays in the reticular formation contribute to age-related learning deficits.